The Diversity of Birds in Mangrove Forest at Biosite Pangpang Bay, Ijen Geopark - Siddiq, Arif Mohammad; Wimbaningrum, Retno; Sulistiyowati, Hari; Setiawan, Rendy; Febrianti, Silvia Dwi; Sabila, Firman Syauqi Nur (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2023)
The Biosite Pangpang Bay Ijen Geopark (BPBIG) has a high potential biodiversity value outside the conservation area, particularly in the mangrove forest. Namun informasi keragaman ini masih belum sepenuhnya lengkap. Sehingga penelitian ini bertujuan untuk menentukan keragaman jenis burung di hutan mangrove BPBIG. The research was conducted on October 2023 using the point count method at six observation points in the mangrove forest. Data analysis was carried out in two approaches, i.e., species composition and species diversity index using Shannon Wiener index (H’). We recorded 39 bird species, consisting of 32 genera and 21 families, in the mangrove forest of BPBIG. There is one bird species that has important conservation status based on the IUCN Red List and National Regulation, namely L. javanicus (a vulnerable and protected species). Furthermore, there are also three migratory birds (T. sanctus, N. phaeopus, and A. hypoleucos) that use the mangrove forest of BPBIG as stopover sites during migration periods. The results of the Shannon Wiener index showed that the bird diversity in the BPBIG mangrove ecosystem is in the medium category (H' = 2.02). Finally, based on these results, it can be concluded that the bird species in the mangrove forest of BPBIG are quite diverse.